Application of Comet assay to assess the effects of white bean meal on DNA of human lymphocytes - Luciana Lopes Silva Pereira; Silvana Marcussi; Lívia Cabral Sátiro; Chrystian Araujo Pereira; Larissa Fonseca Andrade; Lisete Chamma Davide; Custódio Donizete dos Santos (Universidade de São Paulo, 2012)
This study was conducted to evaluate the potential induction of genotoxic effects of white bean flour using the Comet assay. The test was conducted with human lymphocytes present in whole blood immediately after collection, by incubation with white bean flour in three concentrations (3.92, 9.52 and 18.18 mg/mL) at 37 ºC for 4 h followed by preparation of slides. Samples were considered positive (above 20% damage) when the damage observed to cellular DNA was higher than the negative control. No genotoxic potential was found at the doses tested. However, it would be premature to suggest absence of risk to human health of DNA damage since the exposure of cells to the extract was restricted to four hours rather than a whole cell cycle. Additionally, further information on toxicology should be obtained in future studies. Este estudo foi realizado para avaliar o potencial de indução de efeitos genotóxicos da farinha de feijão branco utilizando o teste do Cometa. O ensaio foi realizado com linfócitos humanos presentes no sangue imediatamente após a coleta, por incubação com farinha de feijão branco em três concentrações (3,92, 9,52 e 18,18 mg/mL) a 37 ºC por 4 h, seguida de preparação das lâminas. As amostras foram consideradas positivas (acima de 20% de dano), quando os danos observados no DNA celular foram maiores do que o controle negativo. Verificou-se que as doses testadas não mostraram potencial genotóxico. No entanto, seria prematuro fazer recomendações sobre o padrão de riscos para a saúde humana resultantes de danos ao DNA já que exposição das células ao extrato foi restrito ao período de quatro horas e não durante um ciclo celular completo. Além disso, outras informações sobre a toxicologia devem ser obtidas no futuro.